(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The findings of a research on algae as a biosorbent for heavy metal removal from Tannery wastewater. The study’s objectives included starting the metal bio-sorption process using pure and mixedcultures, administering metal ions to the model solution, and exposing the population to metal-containingwastewater. Various exposure periods were used to compare exposed samples’ rates of metal biosorptionto those of control samples to keep tabs on the process. The findings of this investigation indicate theefficiency of chlorophyta in the heavy metal biosorption process.